MENINGKATKAN HASIL BELAJAR IPA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW - REZKI, MAESTA (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2024)
This scientific paper was motivated by the fact that Science (IPA) learning in classrooms has not yet achieved optimal results. Low academic scores and weak enthusiasm among students are the main challenges. One of the causes is the lecture-based teaching approach, which is "Teacher Oriented," making students passive recipients without opportunities to be active and creative. To address this issue, a Classroom Action Research (CAR) was conducted using the Jigsaw Cooperative Learning Model in two cycles. Each cycle consisted of three sessions, with each session lasting 2x40 minutes. Initially, the learning process progressed slowly as students were unfamiliar with this model. The teacher needed extra time to explain the roles of students within the core and expert groups. However, through repeated explanations, students began to understand and actively participate. Group dynamics improved, although some students were still less focused. The jigsaw model encouraged previously passive students to become active through group interactions, peer support, and a sense of camaraderie. As a result, students successfully completed both individual and group tasks. Qualitatively, the jigsaw cooperative learning model enhanced students’ motivation to actively engage in the learning process. Quantitatively, this method significantly improved students’ academic performance, particularly in Science subjects. Thus, this model offers an effective solution to overcoming classroom learning challenges. ABSTRAKPenulisan karya ilmiah ini didasari oleh kenyataan bahwa pembelajaran Ilmu Pengetahuan Alam (IPA) di kelas belum mencapai hasil maksimal. Rendahnya nilai akademik dan lemahnya antusiasme siswa menjadi tantangan utama. Salah satu penyebabnya adalah pendekatan pembelajaran ceramah yang bersifat "Teacher Oriented," yang menjadikan siswa sebagai objek tanpa memberi kesempatan untuk aktif dan kreatif. Berdasarkan hal tersebut, dilakukan Penelitian Tindakan Kelas (PTK) menggunakan model pembelajaran Kooperatif Tipe Jigsaw dalam dua siklus. Setiap siklus terdiri dari tiga pertemuan dengan durasi 2x40 menit per pertemuan. Awalnya, pembelajaran berjalan lambat karena siswa belum familiar dengan model ini. Guru membutuhkan waktu tambahan untuk menjelaskan peran siswa dalam kelompok inti dan ahli. Namun, dengan pengulangan penjelasan, siswa mulai memahami dan berpartisipasi aktif. Dinamika kelompok berkembang baik, meskipun beberapa siswa masih kurang fokus. Model jigsaw mendorong siswa pasif menjadi aktif melalui interaksi kelompok, dorongan teman, dan nuansa kebersamaan. Hasilnya, siswa mampu menyelesaikan tugas-tugas individu dan kelompok dengan baik. Secara kualitatif, pembelajaran kooperatif tipe jigsaw meningkatkan motivasi siswa untuk berpartisipasi aktif. Secara kuantitatif, metode ini terbukti meningkatkan nilai akademik siswa, khususnya pada mata pelajaran IPA. Dengan demikian, model ini dapat menjadi solusi efektif untuk mengatasi kendala pembelajaran di kelas.